2017
DOI: 10.1002/acr.23269
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Behavior Changes in the Early Rheumatoid Arthritis Period and Risk of Mortality During Thirty‐Six Years of Prospective Followup

Abstract: Objective. To investigate whether rheumatoid arthritis (RA) diagnosis influences smoking behavior changes and whether these changes were associated with mortality. Methods. We identified an incident RA cohort in the Nurses' Health Study (NHS; 1976-2012. Behavioral data were collected through biennial questionnaires. We created a comparison cohort, matching RA cases to women without RA by age and calendar year at the index date of RA diagnosis. To investigate smoking behavior changes in the early RA period, sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…The increased mortality risk for patients with rheumatoid arthritis (RA) compared to the general population may be attributable to altered immunity, medication side effects, systemic effects of inflammation, worsened physical function, accumulation of multimorbidities, and excessive unhealthy behaviors such as smoking . The contribution of metabolic and inflammatory factors (such as obesity) to RA etiology and outcomes has received increased attention recently .…”
mentioning
confidence: 99%
“…The increased mortality risk for patients with rheumatoid arthritis (RA) compared to the general population may be attributable to altered immunity, medication side effects, systemic effects of inflammation, worsened physical function, accumulation of multimorbidities, and excessive unhealthy behaviors such as smoking . The contribution of metabolic and inflammatory factors (such as obesity) to RA etiology and outcomes has received increased attention recently .…”
mentioning
confidence: 99%
“…Instead, we found that health care factors, such as being new to rheumatology care and the health system, were more predictive of smoking cessation. The observed increased likelihood of quitting in patients new to rheumatology care may partially be due to cessation following a new RA diagnosis, a phenomenon previously reported in RA and other chronic diseases (8–10,14,25). Despite their worse RA prognosis, seropositive patients were 43% less likely to quit smoking (26,27).…”
Section: Discussionmentioning
confidence: 59%
“…Patients with RA who continue smoking for at least 5 years after RA diagnosis are at even greater risk of death than smokers without RA and patients with RA who quit smoking (8). While patients are more likely to quit smoking after diagnosis of a smoking‐related chronic disease, research shows that most will continue to smoke (8–10). Further, most patients with RA are not aware of the associations between smoking and RA development and complications (11), although such knowledge could influence cessation attempts.
Despite recognition of smoking as a risk factor for poor rheumatoid arthritis (RA) outcomes, little is known about what predicts smoking cessation among patients with RA. We found that health system factors were more predictive of smoking cessation than patient sociodemographic factors, highlighting the value of implementing health system interventions for smoking cessation. Patients new to rheumatology care were 60% more likely to quit smoking, while seropositive patients were 43% less likely to quit smoking.
…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations